Writing Style: Analyzing How the Students Express Their Ideas in Descriptive Paragraph - Uyun Nafiah (INOVISH JOURNAL, 2019)
This research was done to analyze how the students’ writing styles are in their descriptive paragraph in terms of sentence structure, word choice, degree of details and descriptions, and degree of formality. This is a descriptive qualitative approach with content analysis method. The sample of this study was 26 of fifth semester students of English Education Program UIN TS Jambi academic year 2018/2019. Technique of collecting the data was by documenting students’ descriptive paragraph writing and doing semi structure interview.  The result finding showed that the students have different style of writing. In terms of sentence structure, some students used many simple sentences in their writing that make their paragraphs are monotonous and boring to read; while a few students used a mixture of these sentence types that make their paragraphs are interested to read and seemed attractive. In terms of word choice, the students’ paragraphs mostly used sensory details and a figurative language of simile in describing the object. While in degree of details and description, in general all of students’ paragraphs are specific and descriptive by using prepositional phrases and adding many adjectives to describe the characteristics of the object. In addition, related to degree of formality, in general students’ descriptive paragraphs are casual.